PERBEDAAN HASIL BELAJAR SISWA YANG MENGGUNAKAN MODEL PEMBELAJARAN LANGSUNG DENGAN MODEL PEMBELAJARAN BERDASARKAN MASALAH - Jusuf K, ; Husnul Abid Saputra, (Pendidikan Ekonomi, 2009)
The study intended to find out (1) whether there were any differences in students learning achievement  after the application of the direct instruction  and problem based instruction, (2) whether the learning achievement of  problem-based instruction  was better than that of direct instruction. The population of the study was the tenth graders  which consisted of five classes, whereas, the sample was class X 1 and X 2 taken randomly. The instrument included pretest and posttest. The techniques of data analysis were normality test, homogeneity test, and hypothesis test. The results showed that there were differences in the learning results from the direct instruction and problem based instruction. The problem based instruction yielded better results in learning achievement than direct instruction did.